Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Bùi Ngọc Chương - Bộ Công thương (2016)
Công văn của Bộ Công thương về việc trả lời chất vấn của Đại biểu Bùi Ngọc Chương (Số: 11717/BCT-KH) ngày 06/12/2016